Irony, a Way to Escape Censorship - Toelle, Heidi (Semiotika, 2021)
Among Arab authors, a number of Egyptian writers use irony when addressing a criticism to the politics settled by the authorities. The enunciator of the text is perfectly aware that what he writes, or the speech he assigns to one of his characters, is a false compliment addressed to the government policy, since he intends to say or to make say the very contrary. He manages, at the same time, to put his words, and/or those of his character, in such a context that allows the reader to understand that the apparent meaning of the uttered speech is not what the enunciator, or the character, suggests. This same context also allows the reader to decode the secret meaning, easy to find, considering that the apparent meaning of the speech and its secret one are in relation of contrariety. To demonstrate that, I take as an example a short story published in 1980 by Yûsuf al-Qa‘îd from his collection Hikâyât al-zaman al-djarîh (Tales of the Injured Time).
Keywords: irony; Yûsuf al-Qa‘îd; Hikâyât al-zaman al-djarîh; semiotic square; modalities